2001
DOI: 10.1152/ajprenal.2001.281.5.f920
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of electrogenic sodium-bicarbonate cotransporters pNBC1 and kNBC1 in the rat eye

Abstract: The human NBC1 gene encodes two electrogenic sodium-bicarbonate cotransport proteins, pNBC1 and kNBC1, which are candidate proteins for mediating electrogenic sodium-bicarbonate cotransport in ocular cells. Mutations in the coding region of the human NBC1 gene in exons common to both pNBC1 and kNBC1 result in a syndrome with a severe ocular and renal phenotype (blindness, band keratopathy, glaucoma, cataracts, and proximal renal tubular acidosis). In the present study, we determined the pattern of electrogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 60 publications
4
122
0
Order By: Relevance
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29). Additional studies of the cellular/subcellular localization in various tissues, transport kinetics, and regulation of these electrogenic Na ϩ -HCO 3 Ϫ cotransporters are required to address the question as to why in the mammalian genome there are two distinct genes that encode electrogenic Na ϩ -HCO 3 Ϫ cotransporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29). Additional studies of the cellular/subcellular localization in various tissues, transport kinetics, and regulation of these electrogenic Na ϩ -HCO 3 Ϫ cotransporters are required to address the question as to why in the mammalian genome there are two distinct genes that encode electrogenic Na ϩ -HCO 3 Ϫ cotransporters.…”
Section: Discussionmentioning
confidence: 99%
“…kNBC1 mediates the majority of basolateral HCO 3 Ϫ efflux in the renal proximal tubule (2,9,26,29). pNBC1 is highly expressed in pancreas and various other tissues (1,8,14,20,21). An electroneutral NBC, NBC3 in humans (rat ortholog NBCn1) mediates Cl Ϫ -independent and stilbene-insensitive Na ϩ -HCO 3 Ϫ cotransport in various tissues (10,20,22,25).…”
mentioning
confidence: 99%
“…Insoluble material was removed by centrifugation at 20,000 ϫ g for 15 min at 4°C. The supernatant was pre-cleared with preimmune rabbit serum and protein A-Sepharose resin, and then NBCe1-A protein was immunoprecipitated by a rabbit anti-human NBCe1-A N terminus polyclonal antibody (22). For detailed protocols see Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Ocular defects with NBCe1 mutations (S427L, R298S, R510H) indicate that NBCe1 is critical for fluid homeostasis (glaucoma) and transparency (cataracts) in the eye. Two groups have localized eye NBCe1 isoforms (30,31). Bok and co-workers (31) found that NBCe1-B (pNBCe1) expressed throughout the rat eye (ciliary body, conjunctiva surface cells, cornea, lens epithelium, and retina), whereas NBCe1-A (kNBCe1) was only present in the conjunctiva basal cells.…”
Section: S427l-nbce1 Is An Ion Transport Defectmentioning
confidence: 99%
“…Two groups have localized eye NBCe1 isoforms (30,31). Bok and co-workers (31) found that NBCe1-B (pNBCe1) expressed throughout the rat eye (ciliary body, conjunctiva surface cells, cornea, lens epithelium, and retina), whereas NBCe1-A (kNBCe1) was only present in the conjunctiva basal cells. These investigators postulated that all of the eye pathologies are associated with mutations in pNBCe1.…”
Section: S427l-nbce1 Is An Ion Transport Defectmentioning
confidence: 99%